Sweet charity : the role and workings of voluntary organisations - Hanvey, Christopher P.; Philpot, Terry (Routledge, 1996)
This book focuses on the ever-changing world of charities: the skills needed to manage, fundraise, run a successful lobbying campaign or attract new work and the way in which UK charities will increasingly operate in a European environment.